Comparing traditional and virtual approaches in the micro-excavation and analysis of cremated remains. (August 2020) - Higgins, Owen Alexander; Vazzana, Antonino; Scalise, Lucia Martina; Riso, Federica Maria; Buti, Laura; Conti, Sara; Bortolini, Eugenio; Oxilia, Gregorio; Benazzi, Stefano
Graphical abstract: Highlights: Use of computed tomography and engineering softwares in micro-excavations. Overcoming the destructiveness that is intrinsic to the traditional method. More effective determination of anatomical elements and biological profile. Observation of elements which were not detected by the traditional method. Allowing the acquisition of previously elusive – if not unattainable – information. Abstract: The excavation and micro-excavation of archaeological contexts are, and always have been, destructive operations by definition. This study, although preliminary, has allowed the experimentation and application of computed tomography and engineering softwares (used for the creation and manipulation of three-dimensional surfaces) in micro-stratigraphic archaeological excavations, with the objective to overcome the very destructiveness that is intrinsic to the traditional method. For this purpose, a Roman cremation urn from the monumental necropolis in Via Emilia est – Tangenziale Pasternak (Modena) was chosen as a test subject. The application of this approach consented the analysis of both context and remains as close as possible to their original condition, exhibiting minor fragmentation in comparison with the traditional method which in turn allowed a clearer determination of the individual's biological profile. Moreover, also in virtue of the observation of elements which were not detected by the traditional method, virtual micro-excavation is to be considered a promising approach for the investigation of particular archaeological contexts, enabling greater preservation and enhancing both documentation and analysis.